The Effect of Implementation of the Modern Tax Administration System on Taxpayer Compliance of Free Workers at the Makassar Tax Office - Musseng, Ahmad; Hasanuddin, Rusdia; Umar, Rahmawati (International Journal of Business, Law, and Education, 2023)
This study aims to determine the effect of implementing a modern tax administration system on the compliance of independent worker taxpayers at the Tax office in Makassar. This research used qualitative research methods. Qualitative research is conducted naturally, and the data collected is generally qualitative. This study used data collection techniques through literature review, interviews, and documentation. The results showed that there was an effect of the implementation of the modern tax administration system on taxpayer compliance. The current tax administration system includes (1) organizational structure modernization, (2) organizational procedure modernization, (3) organizational strategy modernization, and (4) organizational culture modernization. This simultaneously and partially affects taxpayer compliance within the Tax Service Office. Placement of employees done by their capacity, capability, reorganization, regeneration, training, and self-capacity development programs. This is done to increase the competence of employees of the Directorate General of Taxes in providing services to taxpayers to improve taxpayer compliance.